PERUBAHAN TRADISI KAMOMOOSE DI KECAMATAN LAKUDO KABUPATEN BUTON TENGAH: 1940-2017 - Siti Fatma; Aslim Hasni Hasan (Jurusan Ilmu Sejarah Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study aims to describe: (1) the background of the birth of Kamomoose in Lakudo District, Central Buton Regency (2) the change in the Kamomoose tradition in Lakudo District of Central Buton Regency in 1940-2017. The method used in this study was a historical method with stages of work, namely; (1) Selection of topics, (2) Gathering of sources, (3) Verification of sources, (4) Interpretation of sources, (5) Historiography (history writing). The results showed that: (1) The Kamomoose tradition was born in the District of Lakudo due to the presence of limbo ano gau (outgoing speech) or vows from someone's mouth. The tradition began in the 1940s and has become an annual event to date. This tradition was preserved as local culture, alms for the construction of mosques, as well as a place to strengthen friendship between the people. (2) The implementation of the Kamomoose tradition consisted of several stages. First, the preparation stage, namely the determination of the time and place of implementation, participants who would follow the Kamomoose tradition, and the tools and materials to be used. Second, the implementation phase. But today, there has been a change in the Kamomoose tradition. First, the change in the Kamomoose tradition arena in 1951-2017. Secondly, the change in fosambu (dissipated) material in the Kamomoose tradition in 1970-2017.Third, the change in the process of carrying out the Kamomoose tradition. Fourth, changes in the values ​​and objectives of the Kamomoose tradition in Lakudo District of Central Buton Regency. Keyword: History, change, tradition, Kamomoose